A Study on Politeness Strategies among Generation X and Y in Islamic Education Classroom - Afriyanti, Naning; Fadilah, Umi Takhammulil; Taufik, Taufik; Sattar, Abdulloh; Budianto, Lestari (Universitas Nusantara PGRI Kediri, 2023)
Communication is one of the activities most often used by humans as a social community, the communication used by someone has differences based on their respective backgrounds. one that affects the form of one's communication is generation. Generation Y and Generation X have different communication styles based on their background. The purpose of this study was to find out the strategies used by Y and X generation Y and X master students in communicating in Islamic education classroom. This study uses a qualitative descriptive method, this method is used to describe data accurately and in depth. based on the results of the research, the strategy used by master students of generations Y and X is a politeness strategy, the politeness strategies of generation Y and X master students differ depending on the situation when communicating.